Differentiation of papillary renal cell carcinoma subtypes by imaging features of CT scan - Techanitisawad, Porjai; Kittikowit, Wipawee; Sasiwimonphan, Kewalee (Chulalongkorn Medical Journal, 2023)
Objective : To identify imaging features of CT scan for type 1 and type 2 papillary renal cell carcinomas (pRCCs); and, to define the findings that can be used to differentiate between these two subtypes. Materials and Methods : Nineteen pRCC tumors recruited into this study were classified as pathology type 1 or type 2. The CT scans of these tumors were reviewed. Imaging features such as tumor size, margins, heterogeneity and enhancement were assessed; and, the findings of type 1 and type 2 tumors were compared. Results : There were 7 type 1 and 12 type 2 tumors. On CT, type 1 tumors had more distinct margin than type 2 tumors (P-value = 0.001) and had more homogeneous density (P-value = 0.020). Type 2 tumors commonly had more infiltrative margins and showed enhancement to a greater degree than type 1 tumors in both corticomedullary and nephrogenic phases of enhancement (P-value = 0.011, 0.048, respectively). Conclusion : On CT, there are some significant differences imaging features between type 1 and type 2 papillary renal cell carcinomas; Type 1 tumors show more distinct margin and more homogeneous density than type 2. Type 2 tumors show greater enhancement degree than type 1 tumors in both corticomedullary and nephrogenic phases.